Phenomenology Analytical Thinking With Open Approach Of Students According To The Assessment Of Learning Mathematics In The 21St Century - et. al., Kanoknapa Erawun, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this article is to describe the phenomenology of analytical thinking with open method students based on the assessment of 21st-century mathematics learning, it was found that the phenomenology of analytical thinking with the open method of students was based on the assessment of learning. Know mathematics in the 21st century, both of which are 4 steps of the Open Approach in math class. It is characterized by a phenomenology, ideology, mentioned as an independent idea of ​​the subject to be studied. To describe the meaning that is built into the conscious mind, the student must not have prejudice. And there is no bias in the subject studied by eliminating one's opinion from what we are studying (bracketing) the focus on purpose. The intentionality and essence of a person's perception are believed that human beings can understand what is experienced through it. In summary, by linking math ideas for this step, teachers will allow students to display individual work or group work on the front board for students to join the class. Moreover, if possible, teachers are advised to show all student work. Although there may be jobs with similar or similar concepts. The work is not complete. Or works with errors Teachers should therefore be able to positively express the student's works or ideas, and then gradually. Correct incorrect ideas from exchanging and suggesting from fellow students.